2017
DOI: 10.4172/2167-7182.1000400
|View full text |Cite
|
Sign up to set email alerts
|

The New Rural Pension Scheme and Family Support and Relationship-Perspectives of Older Adults and Their Children in Rural China

Abstract: Objective: Guided by three theoretical models, this study examined how the formal social insurance policy of the new rural pension scheme (NRPS) in China affected the informal support and relationship between older adults and their adult children as well as among children. Methods:We conducted interviews for older adults in 20 rural families in the center part of China in 2014. Grounded theory approach was used to delineate the codes or themes. Results:The results from the qualitative interview showed that alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Children’s intergenerational support is often an important guarantee for older adults to obtain subjective well-being, which may alleviate depression in older adults [ 9 , 10 , 11 , 12 ]. Study had shown that pensions affected children’s intergenerational support for their older parents [ 13 ]. As a steady source of income, empirical studies also showed that the pension system played an important role for older people to improve their mental health [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Children’s intergenerational support is often an important guarantee for older adults to obtain subjective well-being, which may alleviate depression in older adults [ 9 , 10 , 11 , 12 ]. Study had shown that pensions affected children’s intergenerational support for their older parents [ 13 ]. As a steady source of income, empirical studies also showed that the pension system played an important role for older people to improve their mental health [ 14 ].…”
Section: Introductionmentioning
confidence: 99%